Pregnancy rate and outcomes after uterine artery embolization for women: a systematic review and meta-analysis with trial sequential analysis - Yan, Xiaoli; Zhou, Le; He, Guolin; Liu, Xinghui (Frontiers in Medicine, 2023)
Objective The assessment of the relative impacts of uterine artery embolization (UAE) treatment for female patients is a critical field that informs clinical decisions, yet there is a noticeable scarcity of high-quality, long-term comparative studies. This meta-analysis aimed to focus on the pregnancy rate and outcomes in female patients following UAE and to conduct subgroup analyses based on different patient populations or various control treatments. Methods A systematic literature search was conducted on 2 August 2023 through the Web of Science, PubMed, Embase, and the Cochrane Library of Clinical Trials for all potential studies. Relative risks (RRs) with 95% confidence intervals (CIs) were applied to compare pregnancy rates and outcomes between the UAE group and the control group. Heterogeneity was evaluated statistically by using the chi-square-based Cochran’s Q test and Higgins I2 statistics, and 95% prediction interval (PI). Software R 4.3.1 and Stata 12.0 were used for meta-analysis. The trial sequential analysis (TSA) was performed with TSA v0.9.5.10 Beta software. Results A total of 15 eligible studies (11 cohort studies, 3 randomized controlled trials, and 1 non-randomized clinical trial) were included in this meta-analysis. The overall results revealed that UAE significantly decreased postoperative pregnancy rate [RR (95% CI): 0.721 (0.531–0.979), 95% PI: 0.248–2.097] and was associated with an increased risk of postoperative PPH [RR (95% CI): 3.182 (1.319–7.675), 95% PI: 0.474–22.089]. Analysis grouped by population indicated that UAE decreased the risk of preterm delivery [RR (95% CI): 0.326 (0.128–0.831), p = 0.019] and cesarean section [RR (95% CI): 0.693 (0.481–0.999), p = 0.050] and increased the risk of placenta previa [RR (95% CI): 8.739 (1.580–48.341), p = 0.013] in patients with UFs, CSP, and PPH, respectively. When compared with myomectomy, HIFU, and non-use of UAE, UAE treatment was associated with the reduced risks of preterm delivery [RR (95% CI): 0.296 (0.106–0.826)] and cesarean section [(95% CI): 0.693 (0.481–0.999), p = 0.050] and increased placenta previa risk [RR (95% CI): 10.682 (6.859–16.636)], respectively. Conclusion UAE treatment was associated with a lower postoperative pregnancy rate and increased risk of PPH. Subgroup analysis suggested that UAE was shown to decrease the risk of preterm delivery and cesarean section and increase placenta previa risk. Systematic review registration:https://www.crd.york.ac.uk/prospero/, Identifier CRD42023448257.